Preparation and characterization of corn starch/PVA/glycerol composite films incorporated with ε-polylysine as a novel antimicrobial packaging material - Yurong Gao; Dapeng Li (e-Polymers, 2020)
Corn starch/polyvinyl alcohol (PVA)/glycerol composite films incorporated with ε-polylysine were prepared, and their properties were investigated. The Fourier-transform infrared (FTIR) spectroscopy indicated that the interactions happened between the amino group of ε-polylysine and hydroxyl group starch/PVA composite films. X-ray diffraction (XRD) analysis showed that the addition of ε-polylysine decreased the intensity of all crystal peaks. Thermogravimetric (TGA) analysis suggested that ε-polylysine improved the thermal stability of composite films. Scanning electron microscopic (SEM) analysis showed that the upper surface of composite films incorporated with ε-polylysine presented more compact and flat surface. The antimicrobial activity of the composite film progressively increased with the increasing of ε-polylysine concentration (P < 0.05). The tensile strength, elongation at break and water absorption significantly increased, whereas water solubility decreased with the increasing of ε-polylysine concentration (P < 0.05). Therefore, the corn starch/PVA/glycerol composite films incorporated with ε-polylysine had good mechanical, physical and antimicrobial properties and could have potential application as a novel antimicrobial packaging material.